2018
DOI: 10.1016/j.bonr.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial relationship between bone formation and mechanical stimulus within cortical bone: Combining 3D fluorochrome mapping and poroelastic finite element modelling

Abstract: Bone is a dynamic tissue and adapts its architecture in response to biological and mechanical factors. Here we investigate how cortical bone formation is spatially controlled by the local mechanical environment in the murine tibia axial loading model (C57BL/6). We obtained 3D locations of new bone formation by performing ‘slice and view’ 3D fluorochrome mapping of the entire bone and compared these sites with the regions of high fluid velocity or strain energy density estimated using a finite element model, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 44 publications
2
59
0
Order By: Relevance
“…This is similar to the results obtained from 26-week-old mice that underwent mechanical loading, which had higher bone remodelling on the periosteal surface at the proximal end, and on the endosteal surface at the diaphysis (Birkhold et al 2017). In contrast, 3D fluorochrome mapping results obtained in a non-loaded contralateral control leg at week 22 showed that bone formation was located mainly on the endosteal surfaces (Carriero et al 2018). The predicted overlap using subjectspecific parameters from weeks 14-16 and 20-22 were similar, demonstrating the robustness of the model.…”
Section: Figsupporting
confidence: 87%
See 4 more Smart Citations
“…This is similar to the results obtained from 26-week-old mice that underwent mechanical loading, which had higher bone remodelling on the periosteal surface at the proximal end, and on the endosteal surface at the diaphysis (Birkhold et al 2017). In contrast, 3D fluorochrome mapping results obtained in a non-loaded contralateral control leg at week 22 showed that bone formation was located mainly on the endosteal surfaces (Carriero et al 2018). The predicted overlap using subjectspecific parameters from weeks 14-16 and 20-22 were similar, demonstrating the robustness of the model.…”
Section: Figsupporting
confidence: 87%
“…Although the regions of remodelling generally matched with the SED distribution ( Supplementary Fig. S2), it is slightly different from the bone remodelling observed in the murine tibia loading model, where bone formation has been reported to occur on the medial surface and the interosseous crest (Carriero et al 2018;Pereira et al 2015). Both SED and ε maxprinc as the stimulus were able to predict bone apposition on both the endosteal and periosteal surfaces (Fig.…”
Section: Figmentioning
confidence: 65%
See 3 more Smart Citations